Why Do Vocational High School Students Opt for College? - Wonseok Seo; Changhoon Lee (MDPI AG, 2024)
This study aims to elucidate how-and the underlying significance of their doing so-Korean vocational high school students decide to pursue university education rather than entering the workforce. Drawing on autoethnographic journals, the research employs a combination of Chang's descriptive-realistic, confessional-emotive, and analytical-interpretive writing methods to convey personal experiences, including the background of students and their motivations for opting for university. As an autoethnographer, I have encountered the societal perceptions of Korean vocational high schools, issues with school curricula, and misunderstandings surrounding employment. Over time, I chronicled the documented process of choosing university education, and this has been facilitated by conversations with the homeroom teacher; I have endeavored to elucidate the sociocultural implications of each student's experience through interpretive methods. This study's findings are anticipated to enhance the understanding of the fundamentals of career education in the realm of secondary vocational education and to offer a valuable reference for vocational high school educators on how to guide their students effectively. Furthermore, it should provide educational perspectives and fresh insights for vocational educators and researchers worldwide, thereby facilitating enhancements in career education policies and systems for vocational students.